Death that Came to Holiday, in Stories of E.A. Poe, I. Bunin and V. Nabokov - V. Yu. Lebedeva (Научный диалог)
The results of a comparative analysis of “The Mask of the Red Death” by E. A. Poe, “The Gentleman from San Francisco” by I. Bunin and “The Wing Blow” by V. Nabokov are presented in the article. The relevance of the study is due to the fact that it allows shedding additional light on the Russian reception of E. A. Poe, identifying a number of intertextual echoes, and also contributing to the development of literary thanatology. The author notes that the works show an attempt to escape from death on the “island of pleasure”, doomed to failure. The chronotope of the holiday, which is dominated by mortality, is studied in detail. It is argued that the characters are united not only by their material status, but also by their spiritual one: the authors pose the problems of metaphysical decay, life-sleep, tabooing of death, apostasy, and the proximity of the infernal. It is shown that death in the stories is a subject interacting with people in one way or another, but its “character” in the stories is different. It is proved that the writers also turn to the biblical discourse, focusing on the eschatological aspect. It concludes that the author's intentions are very similar, each story can be read as a parable, and “The Beat of the Wing” turns out to be a kind of “connecting node” between them.